Effective proposal writing - Murthy, Vasudev (Sage, 2006)
This useful book demystifies a very important part of formal business practice--writing a quality proposal. It will help the reader put together a comprehensive, convincing and professional document. Covering all elements that are crucial for writing an effective business proposal, the book also spells out when and under what conditions a proposal should be submitted, the information required, and the ethical business issues involved. Vasudev Murthy provides useful tips for producing a professional document that will enable the writer to establish the credibility of his organization and persuade the reader to accept the proposal. Written in an informal yet practical and engaging style, this book will be invaluable for a varied readership of professionals--whether an independent consultant or a decision-maker within a large organization; the head of an NGO applying for grants, or a manager looking for new business opportunities.